Pengujian Aplikasi Pemesanan Tiket Kereta berbasis Website Menggunakan Metode Black Box dengan Teknik Equivalence Partitioning - Trengginaz, Riro Bregas; Yusup, Ade; Sunyoto, Daniel Sovian; Jihad, Muhammad Ruhul; Yulianti, Yulianti (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2020)
The train ticket booking application is an important application because it involves financial transactions. If something goes wrong can be detrimental to the parties involved. The developer of the train ticket booking application must be able to provide a guarantee that the application has been made according to the requirements and has good quality. To provide a guarantee can be done by testing the application. Testing on a product intends to check if a program has been running as per its capacities or still have blunders that should be adjusted so as to have a decent quality program. A famous testing strategy and broadly utilized by analyzers to investigate the program works out in a good way or not is Black Box Testing and White Box Testing. In this examination, the product that will be surveyed utilizing Black Box Testing is a train ticket booking framework that has two structures: the login structure and the booking type of the train pass to be filled by the administrator. The application will test utilizing Black Box Testing in which the test is just planned to see whether the program is as per the capacity that the program needs without realizing the program code utilized. The sort of testing of the Black Box Testing technique shifts one of which is Equivalence Partitions utilized by the creators in this investigation. Comparability Partitions procedure is a test dependent on entering information on each structure on the framework, each info menu will be tried and assembled by work either legitimate or invalid. Incorrect test results can be found and corrected immediately. So after testing, all requirements have been met and can be guaranteed that the train ticket booking application that has been made is error free and meets all the requirements specified.